2018
DOI: 10.1038/s41598-018-21550-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weight changes on the incidence of diabetes mellitus: a Korean nationwide cohort study

Abstract: Obesity is a well-known risk factor for type 2 diabetes, but few data exist on the association between weight changes and diabetes risk in non-obese subjects. This study aimed to investigate the effect of weight changes on the incidence of type 2 diabetes in Korea, using 51,405 non-diabetic subjects. Individuals who developed type 2 diabetes were more likely to be older and male, to have high body mass index (BMI), blood pressure, fasting blood glucose, and total cholesterol, to be current smokers and frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…Approximately half of the studies reported that WLW is related to a reduced T2D incidence. [8][9][10][11][12] These studies were all based on large samples (n=1929-114 281) from established cohort studies, for example, Nurses' Health Study, 8 The Health Professionals Follow-up Study, 10 National Health and Nutrition Examination Survey 12 and The British Regional Heart Study. 11 Other studies have failed to find any association between WLW and T2D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately half of the studies reported that WLW is related to a reduced T2D incidence. [8][9][10][11][12] These studies were all based on large samples (n=1929-114 281) from established cohort studies, for example, Nurses' Health Study, 8 The Health Professionals Follow-up Study, 10 National Health and Nutrition Examination Survey 12 and The British Regional Heart Study. 11 Other studies have failed to find any association between WLW and T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiology/Health services research (HR of intervention group vs control group 0.61; 95% CI 0.48 to 0.79; p<0.001). 7 These findings are supported in part [8][9][10][11][12] but not all [13][14][15][16] cohort studies with weight loss without information on intentionality (WLW) as an exposure. In these WLW studies, as no information exists on the intentionality of weight loss, the weight-losers may also include individuals with unintentional weight loss.…”
mentioning
confidence: 94%
“…Practically speaking, this should be individualized. While some studies have shown that weight loss is significantly associated with a lower risk for diabetes both in obese and non-obese patients, others have reported adverse effects of losing weight in lean patients [26]. The major pathophysiology appears to be a rapid beta-cell failure due to higher prevalence and early initiation of insulin use.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Type 2 DM was de ned as an FPG level ≥ 126 mg/dL or at least one claim per year for the prescription of hypoglycemic drug under ICD-10 codes E11-14. [19] Patients with type 1 DM who had claims under ICD-10 code E10 were excluded from this study. [20,21] The group with DM < 5 years was de ned as who had type 2 DM with 5 years on the date of the health checkup.…”
Section: Glycemic Status and De Nition Of Chronic Diseasementioning
confidence: 99%